Law No. 28 of the Year 2023 Amending Certain Provisions of Law No. 26 of the Year 1975 on the Egyptian Nationality = قانون رقم 28 لسنة 2023 بتعديل بعض أحكام القانون رقم 26 لسنة 1975 بشأن الجنسية المصرية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic